L'uso di UAV per monitorare e gestire il territorio nel corso di eventi legati al dissesto Geo-idrologico - Giordan, Daniele; Facello, Anna; Allasia, Paolo; Manconi, Andrea; Baldo, Marco; Dell'Anese, Federico (GEOmedia, 2014)
In the last decades, the people and the societies are becoming more vulnerable to natural disasters and environmental emergencies to society. In this context, Unmanned Aerial Vehicles (UAVs) have been increasingly considered for remote sensing operations in civilian contexts and they play an important role in emergency management. Here, we present some preliminary results of test study related to the possible use of UAVs in the field of geo-hydrological hazards.